128 - PREVALENCE OF CHRONIC PAIN IN ELDERLY WOMEN AND ITS RELATIONSHIP WITH QUALITY OF LIFE (Fiep Bulletin - online, 2011)
When it is considered,here,that chronical pain can be a predisponent factor to the depletion of the quality of life of om old age people,the goal of this paper was to avaliate the midex of this paper was to avaliate the midex of chromical pain among old age people attended at a old age people´s centre in the city of São Luís and the link of it with the loss of quality of life those ones. This sample is constitud of 64 old age persons under between 60-78 years old selected freely in which it was applied the tests of pain by EAV and quality of life by (WHOQL-OLD) of OMS, the statistical treatment of the data was perfomed through a statistical analysis in the variables pain and quality of life when in was used descriptive and interferential statistical technics, through the use of the test t-student, of test qui-square (to tablets of contingence 2x2), to the level of 5% of significance (a value – p< 0,05 is a significant result indicating a decision of rejecting the will hypothesis (Ho), to each test applied in this paper. In statiscal analysis performed whit test Qui-square indicative of sings of pain and quality of life, with age group, it was established a P
Keywords: Old age women; Pain; Quality of life